Thresholds of physical activity associated with obesity by level of sedentary behaviour in children. Issue 7 (24th March 2018) - Chaput, J.‐P.; Barnes, J. D.; Tremblay, M. S.; Fogelholm, M.; Hu, G.; Lambert, E. V.; Maher, C.; Maia, J.; Olds, T.; Onywera, V.; Sarmiento, O. L.; Standage, M.; et al.
Summary: Background: It is unknown whether moderate‐to‐vigorous physical activity (MVPA) thresholds for obesity should be adapted depending on level of sedentary behaviour in children. Objective: The objective of the study is to determine the MVPA thresholds that best discriminate between obese and non‐obese children, by level of screen time and total sedentary time in 12 countries. Methods: This multinational, cross‐sectional study included 6522 children 9–11 years of age. MVPA and sedentary time were assessed using waist‐worn accelerometry, while screen time was self‐reported. Obesity was defined according to the World Health Organization reference data. Results: Receiver operating characteristic curve analyses showed that the best thresholds of MVPA to predict obesity ranged from 53.8 to 73.9 min d −1 in boys and from 41.7 to 58.7 min d −1 in girls, depending on the level of screen time. The MVPA cut‐offs to predict obesity ranged from 37.9 to 75.9 min d −1 in boys and from 32.5 to 62.7 min d −1 in girls, depending on the level of sedentary behaviour. The areas under the curve ranged from 0.57 to 0.73 ('fail' to 'fair' accuracy), and most sensitivity and specificity values were below 85%, similar to MVPA alone. Country‐specific analyses provided similar findings. Conclusions: The addition of sedentary behaviour levels to MVPA did not result in a better predictive ability to classify children as obese/non‐obese compared with MVPA alone.